PENGARUH LIKUIDITAS DAN EPS TERHADAP AUDIT DELAY PERUSAHAAN YANG TERDAFTAR DI JII PERIODE 2019-2021 - Ika Yulia Sari; Youdhi Prayogo; Puteri Anggi Lubis (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Liquidity and Earning Per Share on audit delay in companies registered on Jakarta Islamic Index for the 2019-2021 period. To obtain data, the authors use a type of quantitative research, namely by accessing company financial reports. The samples used in this study were 16 companies registered on JII for the 2019-2021 period by passing through the purposive sampling stage in accordance with the criteria needed for research. The data analysis method is in This study uses panel data regression techniques. The results of the study show that: Partially, liquidity does not have a significant impact on audit delay for companies listed on the Jakarta Islamic Index for 2019-2021. The liquidity variable has a p-value of 0.4729 which is greater than 0.05 and a tcount value of 0.726983 which is less than 1.67943 This proves that the liquidity variable has no significant effect on audit delay. Partially Earning per share affects audit delay in companies listed on the Jakarta Islamic Index for 2019-2021. The earning per share variable has a p-value of 0.0273 which is smaller than 0.05 and the tcount value is -2.321091 which is greater than 1.67943. This proves that the earnings per share variable has a negative influence on audit delay. Simultaneously liquidity and earnings per share have a significant effect on audit delay for companies listed on the Jakarta Islamic Index for 2019-2021. Based on the Fcount value is greater than Ftable where 31.68031 > 4.05 and the significance value of the above test is 0.000 <0. 05 (α = 5%).